Single and combined effects of body composition phenotypes on carotid intima‐media thickness. Issue 4 (22nd July 2015) - Melo, X.; Santa‐Clara, H.; Santos, D. A.; Pimenta, N. M.; Pinto, R.; Minderico, C. S.; Fernhall, B.; Sardinha, L. B.
Summary: Background: Central fatness might be a more sensitive predictor of atherosclerotic changes in children than are total body fat measures. However, it is unclear whether a total body fat measure coupled with an estimate of a more central pattern of fat accumulation predicts increased carotid intima‐media‐thickness (cIMT) better than either measure alone. Objective: The objective of the study is to identify the ability of a combination of simple anthropometric screening tools or a combination of objective measures of body composition to predict cIMT. Methods: cIMT was assessed on the common carotid artery in 349 children aged 11–12 years old (183 girls). Body mass index (BMI), waist circumference (WC) and waist‐to‐height ratio (WHtR) were dichotomized according to established criteria and indices of total body (TBFI) and abdominal (ABFMI) fat were assessed by dual‐energy X‐ray absorptiometry and categorized (increased risk ≥85%). Single and combined associations among anthropometric and laboratorial measures with the risk of having increased cIMT (≥85%) and discriminatory performance were tested with logistic regression analysis and Receiver Operator Curve analysis. Results: Children with higher total fatness (BMI and TBFI) or higher central pattern of fat accumulation (WC, WHtR and BFMI) were in higher risk for increased cIMT [odds ratio (OR): 2.08–3.24). The risk for increased cIMT was not higher among children who coupled high total and high central fatness (OR: 2.27–3.10). Conclusions: Combination of total and central measures of fat does not improve the prediction of increased cIMT in children. Simple surrogate measures of fatness can be used to predict increased cIMT urging special attention to those children who exhibit increased abdominal fat.